Design of Low Power Wideband Low Noise Amplifier for Software Defined Radio at 100 MHz to 1 GHz - Salleh, Azahari; Abd Aziz, Mohamad Zoinol Abidin; Misran, Mohamad Harris; Mohamad, Najmiah Radiah (Elsevier Ltd., 2013)
This paper describes the design of wideband low noise amplifier (LNA) for mobile software defined radio (SDR) application which targeted to be applied in two-way communication mobile system architecture. The technical specification was deduced from the TIA- 603C standard receiver system sensitivity and intermodulation. The proposed LNA exhibit low power consumption and adopts a negative feedback wideband amplifier topology, operated from 100 MHz to 1 GHz which covers the whole Land Mobile FM Communication Equipment (136 941 MHz) frequency band. The proposed topology solve the RF tracing problem inherited in the targeted frequency and also the problem of economically impractical PCB size rendered by other wideband amplifier methods. The Advanced Design System software is used to perform the simulations. The measured result show the proposed LNA has a stable gain of more than 15 dB, noise figure less than 1.5 dB, S11 and S22 less than -10 dB, with current consumption of 8 mA from voltage supply at 1.8 V.